1994
DOI: 10.1111/j.1469-8137.1994.tb03976.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulphate and antioxidants in needles of Scots pine (Pinus sylvestrisL.) from three SO2‐polluted field sites in eastern Germany

Abstract: SUMMARY'Needles from young and mature Scots pine trees {Pinus sylveslris) were collected at three field sites in eastern Germany, i.e. Menz, Taura, and Gossa, which differed in SO^ pollution. Current and previous year's needles from the polluted sites Taura and Gossa (yearly mean of SO^: 26 ppb) contained approximately 100-120 /^mo! sulphate g~' d. wt, whereas needles from the unpolluted site, Menz (yearly mean of SO^: 3 ppb) contained 30-65//mol sulphate g"' d. wt. The apoplastic sulphate content was in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…This increase could also be an response to environmental pollutions. Polle et al (1994) found a similar phenomenon in Scots pine growing at three field sites in Germany which differed in SO2 pollution. Increase of glutathione content after exposure to SO2 was also stated in needles of spruce (Mehlhorn et al 1986) and pine (Wingsle and H~illgren 1993) due to SO2 fumigation.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This increase could also be an response to environmental pollutions. Polle et al (1994) found a similar phenomenon in Scots pine growing at three field sites in Germany which differed in SO2 pollution. Increase of glutathione content after exposure to SO2 was also stated in needles of spruce (Mehlhorn et al 1986) and pine (Wingsle and H~illgren 1993) due to SO2 fumigation.…”
Section: Resultssupporting
confidence: 58%
“…Numerous studies indicate that oxidative stress evoked by atmospheric pollutants enhances the quantity of low molecular antioxidants such as ascorbic acid (AA) and glutathione , Mehlhorn et al 1986, Schmidt and Kunert, 1986, Sen Gupta et al1991, Polle et al 1994, Baumbusch et al 1998, Kronfus et al 1998 in cells, also in coniferous plants. AA is a very important primary antioxidant (Nijs and Kelley 1991) which reacts with hydroxyl radical, superoxide and singlet oxygen (Buettner and Jurkiewicz 1996) as well as secondary antioxidant, reducing the oxidised form of ec-tocopherol (Padh 1990).…”
Section: Introductionmentioning
confidence: 99%
“…3e and 4e). Two to four-fold higher sulphate concentration in the Scots pine needles of strongly SO 2 polluted site was recorded by Polle et al (1984). Shin and Park (1989) observed a significant positive correlation (r = 0.831; p < 0.01) between ambient air concentrations of SO 2 and foliar S contents around a TPP in Korea.…”
Section: Discussionmentioning
confidence: 92%
“…Li (2003) has reported POD to be very sensitive to pollution and has also suggested its use as a marker for estimating the level of air pollution. Studies of Karjalainen et al (1992) suggested that increased POD activity is a specific indication of SO 2 and NO X pollution and according to Polle et al (1994) in presence of monophenolics it may act as sulfite oxidases. Therefore, an increase in CAT and POD is considered to be linked with resistance to stress and self defense as it shows variation with the plant being studied and also the level of pollutants .…”
Section: Discussionmentioning
confidence: 99%